Mediastinal Hematoma and Tracheal Compression following Transradial Percutaneous Coronary Intervention - Nathaniel R. Smilowitz; Muhamed Saric; Michael J. Attubato; James N. Slater (Case Reports in Cardiology)
Vascular complications from transradial percutaneous coronary intervention (PCI) are rare. We report an unusual case of stridor after PCI due to brachiocephalic artery perforation, pseudoaneurysm formation, and development of a large mediastinal hematoma with tracheal compression. Endovascular repair of the brachiocephalic artery was achieved with covered stent placement at the neck of the pseudoaneurysm. This case highlights the importance of careful guide catheter placement from the right radial approach. Ultimately, rapid diagnosis of vascular perforation, appropriate airway management, and prompt endovascular repair of the injured vessel is critical to the successful management of this life-threatening condition.